2017
DOI: 10.1371/journal.pone.0190246
|View full text |Cite
|
Sign up to set email alerts
|

A wild ‘albino’ bilberry (Vaccinium myrtillus L.) from Slovenia shows three bottlenecks in the anthocyanin pathway and significant differences in the expression of several regulatory genes compared to the common blue berry type

Abstract: Relative expressions of structural genes and a number of transcription factors of the anthocyanin pathway relevant in Vaccinium species, and related key enzyme activities were compared with the composition and content of metabolites in skins of ripe fruits of wild albino and blue bilberry (Vaccinium myrtillus) found in Slovenia. Compared to the common blue type, the albino variant had a 151-fold lower total anthocyanin and a 7-fold lower total phenolic content in their berry skin, which correlated with lower g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 46 publications
2
28
0
Order By: Relevance
“…of anthocyanidin synthase (ANS) in raspberry (Rafique et al, 2016), substrate competition between DFR and FLS in Petunia (Davies et al, 2003) and downregulation of multiple structural genes in albino bilberry (Zorenc et al, 2017). To investigate the determinants of spatial anthocyanin production in wild-type blueberries, we employed an interdisciplinary approach, linking targeted analysis of metabolites and gene transcription, to map the dynamic changes in flavonoid biosynthesis during fruit maturation of the commercial cultivars 'Nui' (Northern Highbush) and 'Velluto Blue' (Rabbiteye).…”
Section: Introductionmentioning
confidence: 99%
“…of anthocyanidin synthase (ANS) in raspberry (Rafique et al, 2016), substrate competition between DFR and FLS in Petunia (Davies et al, 2003) and downregulation of multiple structural genes in albino bilberry (Zorenc et al, 2017). To investigate the determinants of spatial anthocyanin production in wild-type blueberries, we employed an interdisciplinary approach, linking targeted analysis of metabolites and gene transcription, to map the dynamic changes in flavonoid biosynthesis during fruit maturation of the commercial cultivars 'Nui' (Northern Highbush) and 'Velluto Blue' (Rabbiteye).…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, despite these studies, R2R3MYB SG6/SG5 activators of the anthocyanin pathway have not been identified in blueberries ( Jaakola et al, 2010 ; Zifkin et al, 2012 ). Moreover, investigations into anthocyanin production in members of the Myrtilis section of Vaccinium , which unlike highbush blueberry and other members of the Cyanococcus section, have taxa with anthocyanin-colored berry flesh in addition to the skin, have resulted in conjecture that R2R3MYBs of the PA1 type are involved ( Jaakola et al, 2010 ; Primetta et al, 2015 ; Zorenc et al, 2017 ). This includes VmMYBPA1 ( VmMYB2 ) from bilberry ( V. myrtillus ), which has an expression pattern that correlates with anthocyanin accumulation during berry development ( Jaakola et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…This includes VmMYBPA1 ( VmMYB2 ) from bilberry ( V. myrtillus ), which has an expression pattern that correlates with anthocyanin accumulation during berry development ( Jaakola et al, 2010 ). VmMYBPA1 transcript abundance is reduced in the green sections of fruit in which a berry developmental regulatory gene has been silenced ( Jaakola et al, 2010 ) and in fruit of white-fleshed germplasm ( Zorenc et al, 2017 ). Similarly, MYBPA1 expression is reduced in white-fleshed berries of V. uliginosum (bog bilberry) ( Primetta et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many functional pathways, genes and metabolites associated with phenylpropanoid and flavonoid biosynthesis exhibited upregulation in LR berries, especially in later developmental stages. Developmental stage-specific expression pattern, with relatively low expression in early stages, and very high in later stages was exhibited by the paralogues of DFR and CHS, as well as F3′5′H, OMT and LDOX genes, all of which take part in the biosynthesis of anthocyanin, natural pigment of plants, responsible for red, blue and purple colours 57,62,63 . These genes are commonly upregulated in later stages of fruit ripening 12,62 ; for example, high expression of DFR increases the accumulation of anthocyanin content during fruit ripening 62,64 .…”
Section: Discussionmentioning
confidence: 99%